Comparison of sGC activator and sGC stimulator in 5/6 nephrectomized rats on high-salt-diet - Chen, Xin; Xiong, Yingquan; Zeng, Shufei; Delić, Denis; Gaballa, Mohamed; Kalk, Philipp; Klein, Thomas; Krämer, Bernhard K.; Hocher, Berthold (Frontiers in Pharmacology, 2024)
Soluble guanylate cyclase (sGC) stimulators and activators are known to enhance kidney function in various models of chronic kidney disease (CKD) by increasing cyclic guanosine monophosphate (cGMP). Their differential effects on CKD progression, particularly under conditions of oxidative stress, remain unexplored by direct comparative studies. We conducted a side-by-side comparison using 5/6 nephrectomized rats on a high salt diet (5/6Nx+HSD) to evaluate the efficacy of the sGC stimulator BAY 41-8543 and the sGC activator BAY 60-2770 in CKD progression. BAY 41-8543 (1 mg/kg; twice daily) and BAY 60-2770 (1 mg/kg; once daily) were administered by gavage for 11 weeks. The 5/6Nx+HSD model led to increased plasma creatinine, proteinuria, and blood pressure. Both BAY 41-8543 and BAY 60-2770 significantly reduced systolic and diastolic blood pressure to a similar extent but did not improve renal function parameters. Notably, BAY 60-2770 reduced renal fibrosis, including interstitial fibrosis and glomerulosclerosis, whereas BAY 41-8543 did not. These antifibrotic effects of BAY 60-2770 were independent of blood pressure reduction. Proteomic analysis revealed that BAY 60-2770 corrected the upregulation of 9 proteins associated with apoptosis and fibrosis, including Caspase-3, MKK6 (Mitogen-Activated Protein Kinase Kinase 6), Prdx5 (Peroxiredoxin-5), in the 5/6Nx+HSD group. In contrast, BAY 41-8543 had no significant impact on these proteins. sGC activators were more effective than sGC stimulators in reducing renal fibrosis in 5/6 nephrectomized rats on a high salt diet, and this effect was due to modulation of apoptosis-associated proteins beyond the control of blood pressure.